ANALISIS PERHITUNGAN, PENYETORAN, PELAPORAN DAN PENCATATAN PPN PADA PT XX TAHUN 2021 - Romadhon, Desi Dwiyanti; Sukadana, Ida Bagus Nyoman (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This research aims to analyze the implementation calculation, depositing, reporting, and recording of VAT on XX company in 2021 It also explores the suitability with Regulations Number 42 Year 2009, Finance Minister Regulation Number 242/PMK.03/2014, Finance Minister Regulation Number 63/PMK.03/2021 and principle of general tax accounting. This analysis is carried out using qualitative descriptive methods, which collect and analyze the situation of the subject or object in an institutional form, based on the evidence and facts of the object of study. Data used includes periodic VAT returns for 2021, electronic receipts for 2021, input and output tax invoices for 2021, and recording journals for 2021. The results of this research showed that XX Company calculated, deposited, reported, and recorded VAT in accordance with Finance Minister Regulation Number 242/PMK.03/2014, Finance Minister Regulation Number 63/PMK.03/2021 and principle of generally tax accounting.